Polyaniline based nanocomposites as adsorbents and photocatalysts in the removal of organic dyes / Syed Shahabuddin - Syed , Shahabuddin (2016)
Polyaniline (PANI), due to the delocalization of electrons in a continuously overlapped π-conjugated electron system, has been most intensively investigated conjugated conductive polymer. In recent years, enhancing the properties of PANI for its viable commercial applications by incorporating with metal oxides such as in our case, cobalt oxide (Co3O4) and strontium titanate (SrTiO3), as well as organic material such as chitosan and graphene, has been the focus of research to explore its multifunctional abilities such as photocatalysis and adsorption. With the aim to obtain some PANIs based nanocomposites with controlled morphology, enhanced specific surface area and electronic properties, various synthetic pathways have been designed and carried out. This work describes the synthesis of Co3O4 nanocube-doped polyaniline nanocomposites via in situ oxidative polymerization. It was established that Co3O4 nanocube plays an important role in enhancing the surface morphology of PANI and thereby increasing the effective surface area of nanocomposite. The nanocomposite demonstrated enhanced removal of carcinogenic methyl orange (MO) dye (99%) from aqueous solution as compared to bare PANI. Furthermore, PANI was successfully grafted with chitosan to synthesis chitosan-grafted-polyaniline copolymer (ChGP) and Co3O4 nanocube-doped ChGP nanocomposites via oxidative-radical copolymerization for the photocatalytic degradation of methylene blue (MB) dye. Here chitosan acts as flexible matrix which enhances the adsorption of MB (which otherwise shows no affinity towards PANI due to its cationic nature) and the result exhibits enhanced photocatalytic degradation of MB (88%) within 180 minutes upon ultraviolet (UV) light illumination. Alternatively, wide band gap SrTiO3 nanocubes were synthesized through hydrothermal technique and incorporated into PANI matrix via the in situ oxidative polymerization for the photocatalytic degradation of MB dye under visible light. It has been established that upon irradiation under visible light SrTiO3 produces electrons and holes which were trapped in the vacant HOMO orbitals of PANI thereby creating efficient charge separation and mineralizing MB very efficiently (97%) within a short duration of time (90 minutes). Finally, PANI, graphene oxide and SrTiO3 nanocubes comprising ternary nanocomposites were synthesized for the effective removal of cationic and anionic dyes from waste water. Here PANI was synthesized in the presence of graphene oxide and then decorated with SrTiO3 nanocubes via the in situ oxidative polymerization technique where the synthesized nanocomposites were capable of removing MB in 10 minutes and MO in 30 minutes; within a very short duration of time. The photocatalysis and adsorption performance of the newly synthesized nanocomposites reveal that these materials are highly beneficial in designing efficient water treatment systems by harvesting energy from the UV light or natural sunlight and the adsorption phenomenon. It is worth mentioning that all the nanocomposites were synthesized for the first time by the mentioned techniques.